ANALISIS NILAI MORALITAS PADA TOKOH UTAMA DILAN DALAM NOVEL DILAN (DIA ADALAH DILANKU TAHUN 1990) KARYA PIDI BAIQ - Yuli Maryam; Triwanti Juniar Putri; Dida Firmansyah (IKIP Siliwangi, 2018)
Novel is a fictional work based on the author’s imagination. The author writes a novel based on his own experience or sees from the experiences of others. In a novel there are always moral values that deserve an example in everyday life. Value is an important and useful traits for human beings or something that perfects human beings according to their very nature need to understand and apply the norm, values and morals when interacting in the community has several main reasons that one of them is for self-interest. The value of morality is anything related to ethical customs or manners . The author chose the novel Dilan (dia adalah Dilanku tahun 1990) because this novel is popular being warmly discussed by young people. This Dilan novel tells the story of two people who love each other is Dilan and Milea. In this analysis the authors are only focused on the main character ie “Dilan” handsome man, intelligent and a combat commander who became the idol of many women. There are moral examples that can be emulated from Dilan figures to be applied in everyday life, such as religious values, traditional values of dat dynasty immorality value and courtesy values.